REFORM OF HOUSING COMMUNAL SERVICES IN UZBEKISTAN (American Journal of Research in Humanities and Social Sciences, 2023)
The article talks about the radical change in the methods and approaches of financing and management of the housing reform and the related scientific proposals and practical recommendations.